The Private Law State - Davis, Seth (McGill Law Journal / Revue de droit de McGill)

(untitled) (McGill Law Journal / Revue de droit de McGill, 2018)
What legal duties do states owe those subject to their power? Typically, we look to public law to answer this question, defining the powers and duties of governments through constitutional law, administrative law, and international law, which we distinguish from the private law of contracts, property, and tort. It was not always this way, however. Recently, moreover, scholars are again looking to private law doctrines, concepts, and techniques to think about the powers and duties of states. It is a particularly promising moment for private law thinking about the state. The emergence of the “new private law,” as well as the “new legal criticism,” have enriched conceptual analysis and normative debate in private law. Against this backdrop, scholars have turned to private law to think about the powers and duties of states in public law.This Article, occasioned by a symposium on Evan Criddle and Evan Fox-Decent's groundbreaking Fiduciaries of Humanity, takes stock of the private law state. It offers a qualified defense of private law theorizing about state powers and duties. The defense is that private law provides a set of lawyerly techniques for principled normative judgment in a plural world. The qualification is that private law cannot itself determine the solution to normative problems that it itself contains. Thinking about the state in terms of private law offers a way of recapturing normativity for public law, that is, a way of developing a moral brief against conceptions that place state sovereignty outside the rule of law. This transformation is as much as cultural and political as it is doctrinal and conceptual. The project of the private law state would, therefore, be significantly enriched by a critical engagement with the culture of legal practice and the limits of its political vision.